The ANC and its use of history to build its brand - Ronald Irwin (Communicare)
The African National Congress, South Africa’s ruling party since its liberation from apartheid in 1994, has one of the most compelling stories in modern political history. Few political parties in the world have such a momentous, historically moving narrative; and few have used it to such effect. The party has specialised in associating itself with the “collective memory” of the South African people, ensuring that the ANC has been strongly associated with the South African struggle narrative of the twentieth century. This is the heart of the “good story” that has kept the ruling party in power since 1994 and made it very difficult for other political groupings to claim to have played a major role in the struggle for freedom in South Africa.